Optimization of ITO as a Top Layer for Solar Cell Application - Nur Qutren Nada Binti Khyrun Anuar; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2022)
: In solar cells application, ITO thin films can be used as a top layer. ITO can act as a contact layer, current spreading layer and window layer. ITO has a high transparency in the visible range, good electrical conductivity, and wide bandgap energy. P-type silicon (Si) is a semiconductor used in solar cell structure. However, Si causes high reflection of light on the surface which will lower the resistivity of solar cells. Besides, when layer of ITO films were added on top of Si, the mismatch of ITO and Si causes a contact resistance of a potential barrier created between them. In this study, a different thickness of ITO was deposited onto the Si and glass substrates. The samples were characterised based on the optical, electrical, and topological characteristics by using UV-Vis spectrometer, four-point probe and atomic force microscope (AFM), respectively. In optical observation gained from UV-Vis spectrometer, transmittance and bandgap graph were found to be decreasing with the increasing of ITO films thickness. The bandgap values was determined by the absorbance spectrum. Moreover, the electrical analysis gives resistivity values for different thickness of ITO films from four-point probe. The resistivity found to be decreasing exponentially with various thickness of ITO films. In addition, the AFM results show an increment of the grain size along with the thickness. Meanwhile, RMS roughness show exponent increment with the thickness of ITO films. This shows that the properties of ITO depend strongly on film thickness. It is an important parameter in the application of solar cells for ITO as a top layer. Other than that, figure of merit was used to comparing the optical transmittance and sheet resistance between ITO films. From that, the best thickness of 400 nm ITO film with the best properties was obtained.